2020
DOI: 10.1002/onco.13593
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Human Papillomavirus Infection on Skin Cancer: A Population-Based Cohort Study

Abstract: Background This study investigated the correlation between a history of human papillomavirus (HPV) infection and skin cancer risk. Materials and Methods The study cohort comprised 26,919 patients with newly diagnosed HPV infection between 2000 and 2012; with the use of computer‐generated numbers, patients without previous HPV infection were randomly selected as the comparison cohort. The patients in the HPV infection cohort were matched to comparison individuals at a 1:4 ratio by demographic characteristics an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…One of the prospective applications of ddPCR in skin cancer research may be in the field of preventive medicine. Established risk factors for skin cancer include environmental carcinogens, such as ultraviolet (UV) light exposure, immunosuppression, chronic inflammation, genetic background, and infection with certain human papillomavirus (HPV) genotypes [ 79 ]. A bourgeoning body of research highlights an etiologic relationship between HPV infection and skin cancer, particularly between types in genus β and SCC [ 80 , 81 ].…”
Section: The Ddpcr Methods For Primary Prevention Strategies and Pers...mentioning
confidence: 99%
“…One of the prospective applications of ddPCR in skin cancer research may be in the field of preventive medicine. Established risk factors for skin cancer include environmental carcinogens, such as ultraviolet (UV) light exposure, immunosuppression, chronic inflammation, genetic background, and infection with certain human papillomavirus (HPV) genotypes [ 79 ]. A bourgeoning body of research highlights an etiologic relationship between HPV infection and skin cancer, particularly between types in genus β and SCC [ 80 , 81 ].…”
Section: The Ddpcr Methods For Primary Prevention Strategies and Pers...mentioning
confidence: 99%
“…Emerging studies have shown a possible link between SCC and human papillomavirus (HPV). A recent population-based study conducted in Taiwan has found an increased risk of HPV infection in patients with NMSC (adjusted hazard ratio, 2.59; 95% confidence interval [CI], 1.43-1.71) compared with controls [18]. A meta-analysis also found an increased risk of HPV infection in cutaneous SCC than in normal-appearing skin (pooled effect size, 3.43; 95% CI, 1.97-5.98) [19].…”
Section: The Skin Microbiota and Skin Cancer 21 Non-melanoma Skin Can...mentioning
confidence: 99%
“…Several epidemiological studies have suggested the association between HPVs and melanoma. A population-based cohort study demonstrated that a HPV infection is associated with an increased risk of melanoma (adjusted hazard ratio, 17.1; 95% CI, 1.88-156) [18]. As a matter of fact, high-risk mucosal HPVs have been found in 27% of MM samples (skin biopsy) using PCR-ELISA [45].…”
Section: Malignant Melanomamentioning
confidence: 99%
“…Staphylococcus aureus and Cutibacterium were associated with squamous cell carcinomas of the skin [ 161 , 162 ]. Some studies have also found an association between HPV and non-melanoma skin cancers [ 163 ]. In vitro studies have revealed that changes in gut and skin microbiome were associated with the progression of melanomas [ 164 ].…”
Section: Reviewmentioning
confidence: 99%